2019
DOI: 10.7150/thno.35387
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota-inflammation-brain axis in end-stage renal disease: perspectives from default mode network

Abstract: The gut-brain axis in end-stage renal disease (ESRD) is attracting more and more attention. However, the mechanism of gut-brain axis based cognitive disorders in ESRD patients remains unclear. The purpose of this study was to investigate the linkages between the gut microbiota, inflammatory cytokines, brain default mode network (DMN) and cognitive function in ESRD patients.Methods: This prospective study enrolled 28 ESRD patients (13 males and 15 females, mean age of 44 ± 14 years) and 19 healthy controls (HCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 54 publications
(50 reference statements)
2
28
0
Order By: Relevance
“…Our study observed that the change in gut microbiota in patients with ESRD, which was consistent with many literatures ( Wang et al., 2019 ; Hu et al., 2020b ). Besides, gut microbiota was correlated with the clinical indicators of patients, suggesting disease complications and gut microflora dysbiosis may influence each other.…”
Section: Discussionsupporting
confidence: 93%
“…Our study observed that the change in gut microbiota in patients with ESRD, which was consistent with many literatures ( Wang et al., 2019 ; Hu et al., 2020b ). Besides, gut microbiota was correlated with the clinical indicators of patients, suggesting disease complications and gut microflora dysbiosis may influence each other.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding of a positive correlation of Prevotella with DMN and ECN functioning and also fronto-parietal attention network modulations support these results. Previous work showed a link between gut microbiota and restingstate functional connectivity, as assessed here (9,49). Interestingly, in one study assessing bivariate relationships, Prevotella and Bacteroides were associated with insular connectivity (8).…”
Section: Discussionmentioning
confidence: 72%
“…Other exploratory region-of-interest (ROI) analyses did not reveal significant associations. Another resting state fMRI study (n=28 vs 19) demonstrated that in end-stage renal disease, the integrity of the default mode network (DMN) was decreased along with alterations in the gut-microbiota composition (9). Taken together, these results are difficult to integrate and comprehend, as studies focus on one aspect of the modalities, such as connectivity from one particular ROI, or the gut-brain axis in targeted patient groups, or with different types of interventions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that the intestinal tract harbors up to 100 trillion microbes 26 . These gut microbiota maintain the integrity of the epithelial barrier and shape the intestinal immune system, balancing host defense with microbial metabolites, components, and attachment to host cells 96 . Concomitantly, intestinal mucosa contains a large number of different immune cells that participate in the maintenance of a healthy microbiota community, as well as reinforce epithelial barrier functions 97 .…”
Section: The Role Of Gut Microbiota In Iga/gd-iga1 Immunitymentioning
confidence: 99%